(untitled) (Applied Biological Research, 2018)
The present study was aimed to study in vitro differentiation of canine bone marrow mesenchymal stem cells (BMSCs) to islet-like cells of pancreas. BMSCs were isolated from healthy dogs and cultured in laboratory. BMSCs after 3rd passage (at 80% confluence) were induced to differentiate into islet like cells by using 2-step induction methods.Characterization of differentiated cells of BMSC into islet-like cells was done by observing cell morphology, expression of canine insulin gene by reverse transcriptase PCR (RT-PCR) and quantitative PCR (qPCR), detection of nestin and insulin proteins by immunocytochemistry and quantification of insulin level in culture media. Typical grape-like clusters of cells were observed under bright field microscope. Expression of insulin gene and protein was observed in differentiated cells. Insulin level in culture media of differentiated cells was significantly high. It was concluded that canine BMSCs could effectively be differentiated into islet-like cells. These differentiated cells could play an important role in diabetic therapy of dogs.